2013
DOI: 10.1016/j.bbmt.2012.11.616
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Drug Monitoring (TDM) of Cyclosporine Using the Area Under the Curve in Children Undergoing Hematopoietic Stem Cell Transplant (HSCT)

Abstract: All patients Mean AUC24h 21 days (ng.h/mL) Mean C0 21 days (ng/mL) 12 581 Minimum 6531 Maximum 20168 202 Minimum 78 Maximum 430 With GVHD 12 561 p ¼ 0.98 193 p ¼ 0.64 No GVHD 12 590 205 With nephrotoxicity 12 345 p ¼ 0.611 214 p ¼ 0.360 No nephrotoxicity 12 765 193

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Although some studies found no difference in oral absorption profiles of gelatin capsules versus solution [3,68], one has to be cautious because total PK and pharmacodynamic equivalency may not be a fixed rule especially for adverse reactions or monitoring parameters [69][70][71][72].…”
Section: Formulation Differencesmentioning
confidence: 99%
“…Although some studies found no difference in oral absorption profiles of gelatin capsules versus solution [3,68], one has to be cautious because total PK and pharmacodynamic equivalency may not be a fixed rule especially for adverse reactions or monitoring parameters [69][70][71][72].…”
Section: Formulation Differencesmentioning
confidence: 99%